The dilemma of sustainability and price : Young consumers' reasonings regarding Food packaging - Laboutka, Filip (2023)
This study is focused on thoughts of Generation Z regarding the dilemma between price and sustainability. It aims to explore the reasonings this generational cohort has behind their behaviour on an example of food packaging. The selected method used to gather data is in-depth semi-structured interviews. Research method being explorative qualitative research. The core findings are that Generation Z would like to select sustainable food packaging, but can’t due to “green premium” and their economic situation. Generation Z is reasonably knowledgeable about food packaging aspects and related food waste. However, personal contribution to sustainability is lacking. Several observations were made among which were general hatred towards paper straw and packaging design potential. These findings and observations can serve as a strong basis for further research.